Family History of Diabetes and the Effectiveness of Lifestyle Intervention on Insulin Secretion and Insulin Resistance in Chinese Individuals with Metabolic Syndrome - Haiqing Zhu; Xiaoping Chen; Bo Zhang; Wenying Yang; Xiaoyan Xing (Journal of Diabetes Research)
Aims. The current study aims to explore if a family history of diabetes can influence the efficiency of lifestyle intervention on insulin secretion and study the insulin resistance in Chinese men and women with metabolic syndrome in a cohort with a 2-year follow-up. Methods. 151 individuals (90 individuals did not have a family history of diabetes (DMFH (-)) and 61 with a family history of diabetes (DMFH (+)) with metabolic syndrome participated in the lifestyle intervention program at baseline and finished with 1-year follow-up. 124 individuals have two-year follow-up data. A family history of diabetes was ascertained by self-report. Lifestyle interventions were individual sessions on lifestyle changes. Results. During the 1-year follow-up, Ln Insulinogenic index (Δbaseline−1year=0.29±0.65, P=0.001) and 30-min glucose (Δbaseline−1year=−0.41±1.71, P=0.024) changed significantly in the DMFH(-) group; in the DMFH(+) group, Ln ISIm (Δbaseline−1year=−0.22±0.60, P=0.022) and 30-min glucose (Δbaseline−1year=0.53±1.89, P=0.032) changed significantly, and there was no significant change of other parameters. The change of 30 min glucose during a 1-year intervention has shown a significant difference between the two groups (P=0.002). During the 2 years intervention, Ln Insulinogenic index changed significantly in the DMFH(-) group (Δbaseline−1year=0.33±0.66, P<0.001 and Δbaseline−2year=0.43±1.17, P=0.034). Fasting insulin (Δbaseline−2year=2.95±8.69, P=0.034), 2 h insulin (Δbaseline−2year=23.75±44.89, P=0.002), Ln HOMA-B (Δbaseline−2year=0.43±1.02, P=0.009), Ln HOMA-IR (Δbaseline−2year=0.53±1.04, P=0.002), Ln ISIm (Δbaseline−2year=0.52±0.95, P=0.004), and Ln Insulinogenic index (Δbaseline−2year=0.66±1.18, P=0.047) changed significantly after 2 years of intervention, compared to the baseline in the DMFH(+) group. The change of Ln ISIm (P=0.023), fasting (P=0.030), and 2 h insulin (P=0.007) during the 2-year intervention has shown a significant difference between the two groups. Family history of diabetes was related with a 0.500 unit increase in 2-year ISIm (P=0.020) modified by lifestyle intervention adjusted for age, baseline BMI, sex, and baseline waist circumference and a 0.476 unit increase in 2-year ISIm (P=0.027) with extra adjustment for weight change. Conclusions. Patients with a family history of diabetes benefit more from lifestyle intervention in regard to insulin resistance than those without a family history of diabetes adjusting for age, baseline BMI, sex, baseline waist circumference, and weight change.